GROWTH AND SURVIVAL SILVER POMPANO (Trachinotus blochii, Lacepede) WITH DIFFERENT STOCKING DENSITY ARE MAINTAINED IN FLOATING NET CHAGES - Samsul Arif Ashari; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conducted on may 24th to July 24st 2014 at Balai Budidaya Laut Batam. The aim of this research was to determine the effect of stocking density on growth and survival fish silver pompano (Trachinotus blochii, Lacepede) reared in floating net cages. The research method used was experimental method and Complete Random Device (CRD) with three treatments and three replications. The treatments in this study were stocking density silver pompano 40 fishes/m3, 60 fishes/m3, and 80 fishes/m3. To know fish development, body weight and total length was measured every 1 week. The result of the observation showed that the stocking density 60 fishes/m3 the best stocking density in this study which provides absolute growth weights 56,20 gram, total growth length (7,13 cm), specific growth rate (3,28%) and survival rate (99,26%).Keywords : Stocking density, Growth, Survival, Floating net cages, Silver pompano